2011
DOI: 10.1007/s10802-011-9540-4
|View full text |Cite
|
Sign up to set email alerts
|

Affective Functioning Among Early Adolescents at High and Low Familial Risk for Depression and Their Mothers: A Focus on Individual and Transactional Processes across Contexts

Abstract: This study aimed to characterize affective functioning in families of youth at high familial risk for depression, with particular attention to features of affective functioning that appear to be critical to adaptive functioning but have been underrepresented in prior research including: positive and negative affect across multiple contexts, individual and transactional processes, and affective flexibility. Interactions among early adolescents (ages 9-14) and their mothers were coded for affective behaviors acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 58 publications
(83 reference statements)
7
39
2
Order By: Relevance
“…For example, the presence of negative behaviors in a positive context may convey greater risk than negative behaviors in a negative context because, despite being primed for pleasant affect, the behaviors may be more salient and model maladaptive functioning. This is consistent with our previous finding (McMakin et al, 2011) that higher levels of maternal negative interaction behaviors in positive, but not negative, contexts for mothers with a history of depression relative to never depressed mothers. Thus, we explore whether behaviors in negative or positive contexts predict youth depressive symptoms, which was not examined in our previous report.…”
Section: The Present Studysupporting
confidence: 93%
See 3 more Smart Citations
“…For example, the presence of negative behaviors in a positive context may convey greater risk than negative behaviors in a negative context because, despite being primed for pleasant affect, the behaviors may be more salient and model maladaptive functioning. This is consistent with our previous finding (McMakin et al, 2011) that higher levels of maternal negative interaction behaviors in positive, but not negative, contexts for mothers with a history of depression relative to never depressed mothers. Thus, we explore whether behaviors in negative or positive contexts predict youth depressive symptoms, which was not examined in our previous report.…”
Section: The Present Studysupporting
confidence: 93%
“…Mothers are rated on a five-point Likert scale with half-point intervals (1 extremely uncharacteristic to 5 extremely characteristic) for individual affective behaviors. As the present study builds on the cross-sectional work in McMakin et al (2011), we relied on the same observational codes: Positive Affect, Problem Solving, Support/Validation, Negative Affect, Dominance, Conflict, and Withdrawal. Each code was rated separately in each context.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a longitudinal study of 1- to 9-year-old high-risk offspring (n=117) and low-risk peers (n=95), the groups displayed similar developmental trajectories of negative affect across the years, but high-risk offspring had consistently lower levels of positive affect than controls (Olino, Lopez-Duran et al, 2011). This finding complements results from cross-sectional studies, which showed lower levels of positive affect among high-risk offspring than among controls in experimental situations, including in samples of: 1- to 8-year-olds (Shaw et al, 2006), 3- to 4-year-olds (Durbin, Klein, Hayden, Buckley, & Moerk, 2005), 9- to 14-year-olds (McMakin, Burkhouse et al, 2011), and 8- to 17-year-olds (Dietz et al, 2008). Importantly, (compared to affect in low-risk offspring), attenuated positive affect persisted across different laboratory contexts according to high-risk 9- to 14-year-olds and their mothers (McMakin, Burkhouse et al, 2011).…”
Section: Dysphoria and Mood Repair: Clinical And Behavioral Perspectivessupporting
confidence: 85%